Coronavirus Disease 2019 in Autoimmune Hepatitis: A Lesson From Immunosuppressed Patients. Issue 9 (8th July 2020) - Gerussi, Alessio; Rigamonti, Cristina; Elia, Chiara; Cazzagon, Nora; Floreani, Annarosa; Pozzi, Roberta; Pozzoni, Pietro; Claar, Ernesto; Pasulo, Luisa; Fagiuoli, Stefano; Cristoferi, Laura; Carbone, Marco; et al.
Abstract : Chronic immunosuppression is associated with increased and more severe viral infections. However, little is known about the association between immunosuppression and severe acute respiratory syndrome coronavirus 2 (SARS‐CoV‐2) infection. Our aim was to describe the clinical course of patients with immunosuppressed autoimmune hepatitis (AIH) during coronavirus disease 2019 (COVID‐19) infection in Italy. Our study is a case series of patients with AIH treated with immunosuppression, who tested positive for SARS‐CoV‐2 in March 2020 during the outbreak of COVID‐19. Ten patients from seven different hospitals in Italy were diagnosed with COVID‐19 during the outbreak of SARS‐CoV‐2 in March 2020. Seven subjects were female (70%), and age ranged from 27 to 73 years. Before the onset of SARS‐CoV‐2 infection, all patients were taking immunosuppressive therapy for AIH, and eight of them were on biochemical remission. Two other patients had recent acute onset of their AIH, and consequently started high‐dose steroids, as per induction protocol. All patients had a respiratory syndrome and a positive nasal swab for SARS‐CoV‐2. Five patients developed a computed tomography–confirmed COVID‐19 pneumonia. Six subjects received a combination of antiretroviral and antimalarial drugs. In seven patients, the dosage of immunosuppressive medication was changed. Liver enzymes were repeated during SARS‐CoV‐2 infection in all hospitalized cases; they remained within the normal range in all cases, and improved in the two acute cases treated with high‐dose steroids. The clinical outcome was comparable to the reported cases occurring in non‐immunosuppressed subjects. Conclusion: Patients under immunosuppressive therapy for AIH developing COVID‐19 show a disease course presumptively similar to that reported in the non‐immunosuppressed population. These data might aid in medical decisions when dealing with SARS‐CoV‐2 infection in immunocompromised patients. Abstract :